Pengaruh Koneksi Politik, Dimensi CSR dan Board Diversity Terhadap Agresivitas Pajak - Ferry Irawan (Program Studi Akuntansi FPEB UPI, 2022)
One of Indonesia's tax problems is tax aggressiveness done by its taxpayers. This study aims to analyze the effect of political connections, Corporate Social Responsibility (CSR) dimension and board diversity affect corporate tax aggressiveness. The data used is secondary data from manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019. Sampling was conducted using purposive sampling in order to obtain 290 observations. The study found that political connections by the company have a negative effect on corporate tax aggressiveness while board diversity has no effect on aggressive tax actions. The results of the research on CSR dimension variable found that tax aggressiveness depends on the nature of its CSR dimensions. The economic dimension has no influence on tax aggressiveness, the environmental dimension has a significant negative effect and the social dimension has a significant positive effect on aggressive tax action.